Closure of gastric perforations during endoluminal resection using a novel biodegradable collagen sol: A feasibility survival study on porcine model (with video). Issue 1 (22nd March 2021) - Uraoka, Toshio; Yunoki, Shunji; Sasaki, Motoki; Kinoshita, Satoshi; Takatori, Yusaku; Hirai, Yuichiro; Narita, Takefumi; Ramberan, Hemchand; Shimoda, Masayuki; Yahagi, Naohisa
Abstract : Objective: A prior study using porcine colon demonstrated the feasibility of a novel injectable, temperature?responsive, and biodegradable collagen sol (ICS) that transforms from a liquid to a gel state in response to body temperature for endoscopic closure of perforation during endoscopic resection (ER). This study aims to report the acute and survival outcomes of ICS for gastric perforations during ER. Methods: In two experiments using nine live pigs under general anesthesia, four and six perforations (3‐5\xA0mm) were created using an electrosurgical knife in acute and survival experiments, respectively. ICS was delivered to the perforations using an endoscopic catheter. In Experiment 1, a leak test and histopathology were performed on all explanted stomachs after euthanization. In Experiment 2, perforation sites were assessed by gastroscopy and histopathology 7, 14 and 28\xA0days post?procedure. Results: In Experiment 1, gastroscopy confirmed complete closure of the perforations with ICS and no evidence of leak. Subsequent histopathology revealed a fixation of collagen gel (CG) as a sealant agent at the perforation sites. There were no adverse effects related with ESD or the use of ICS. In Experiment 2, histopathology revealed a fixation of CG as a sealant agent, replacement with granulation tissue and no CG; and fibrotic tissue at 7, 14 and 28\xA0days, respectively. Conclusions: This study presents a novel method using ICS, demonstrating promising efficacy and safety profile for endoscopic closure of perforations during ER. Further studies are necessary before translating to clinical use.